Energy harvesting and energy storage systems - Rajput, Shailendra; Averbukh, Moshe; Rodriguez, Noel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book discuss the recent developments in energy harvesting and energy storage systems. Sustainable development systems are based on three pillars: economic development, environmental stewardship, and social equity. One of the guiding principles for finding the balance between these pillars is to limit the use of non-renewable energy sources
Titelrückseite: This is a reprint of articles from the Special Issue published online in the open access journal Electronics (ISSN 2079-9292) (available at: www.mdpi.com/journal/electronics/special issues/ harvesting storage).
Keywords: Energiespeicherung; Energy Harvesting; Mikrogenerator; photovoltaic; parameter extraction; single-diode model; double-diode model; swarm intelligence; wind energy; renewable resources; Black–Scholes model; AC-DC converter; shunt regulator; full bridge rectifier; electrostatic vibration energy harvesting; fully integrated; IoT; charge pump; energy harvesting; thermoelectric; battery efficiency; on-chip integration; power management; supercapacitor; storage unit; unbalanced distribution networks; linear loads; non-linear loads; total harmonic distortion; harmonic power flow; proton exchange membrane fuel cell; parameter identification; energy storage; arithmetic optimization; microgrid; PLL; RTDS; direct power control; fuzzy logic; voltage source inverter; energy autonomous; wearables; energy management; fog edge computing; task offloading; IoMT; sooty tern optimization; distributed generation; equilibrium optimization technique; wind turbines; biomass generators; Aufsatzsammlung